1951
DOI: 10.1021/ja01148a071
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthesis of Purine Nucleosides. The Synthesis of Adenosine, Guanosine and 2,6-Diamino-9-β-D-ribofuranosylpurine1

Abstract: in the number of reactive sites or the dissociation of a urease-inhibitor complex with the inhibitor assumed to be of natural origin. With the recognition that potassium ion can function as an inhibitor and phosphate ion as an activator of urease it appears that neither of the above explanations are correct and that the dilution effect is simply the consequence of a change in the relative concentrations of enzyme, activator and inhibitor.18s19 ExperimentalReagents.-The stock 0.1, 0.2, 0.3, 0.4 and 0.5 $1 buffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

1957
1957
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(45 citation statements)
references
References 1 publication
0
45
0
Order By: Relevance
“…The purity of the purines and purine-containing compounds was determined by ultra-violet spectrophotometry and paper chromatography in suitable solvent systems. The 2,6-diaminopurine riboside (2,6-diamino-9-p-D-ribofuranosyl purine) and the adenine glucoside (9-f8-D-glucopyranosyl adenine) were prepared by the method previously described (10). Samples of purine riboside (9- The results of a typical experiment are presented graphically in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The purity of the purines and purine-containing compounds was determined by ultra-violet spectrophotometry and paper chromatography in suitable solvent systems. The 2,6-diaminopurine riboside (2,6-diamino-9-p-D-ribofuranosyl purine) and the adenine glucoside (9-f8-D-glucopyranosyl adenine) were prepared by the method previously described (10). Samples of purine riboside (9- The results of a typical experiment are presented graphically in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, some of the 9-a-anomer was formed during the migration, with more of the a-anomer being formed with hydrogen halide than with mercuric halide catalysts. This result, coupled with the fact that appreciable quantities of 3-glycosylpurines were isolated from the reaction of chloromercuri-.N-benzoyladenine (3) with 2,3,5-tri-O-benzoyl-o-ribofuranosyl bromide (4), indicates that the actual glycosylation reaction must occur via an initial alkylation at N-3, followed by a rapid migration to N-9 by an intermolecular attack. (16) Further studies revealed that the direct alkylation of .N,.N-dimethyladenine with 2,3,5-tri-O-benzoylribofuranosyl bromide gave a mixture of the 3-and 9-ribosyl derivatives and that the 9-ribosyl isomer was formed by an analogous N-3 --+ N-9 migration.…”
Section: J/5mentioning
confidence: 99%
“…(25) Thus, I-O-acetyl-2,5-di-O-benzoyl-3-acetamido-3-deoxy-n-ribofuranose (15), chloromercuri-N-benzoyladenine (3), and titanium tetrachloride gave a 57 % yield of N-benzoyl-9-(3-acetamido-3-deoxy-2,5-di-Obenzoyl-p-o-ribofuranosyl)adenine (16), which contained some (X-anomer. It was believed that TiCI 4 catalyzed the anomerization of the initially formed 13-…”
Section: N-benzoyladenine With Either 2-deoxy-35-di-o-p-nitrobenzoylmentioning
confidence: 99%
“…Mercuric salts of thymine or theophylline in inert solvents are generally employed for nucleoside synthesis. [2][3][4][5] The condensation of the salts chloride (1)6) in xylene did not give any of the expected nucleoside; instead, a colorless sirup with no chlorine and nitrogen was obtained. It showed a positive resorcin test (Seliwanoff test),7) a strong band due to an enol acetate, a weak band due to a double bond in the infrared, and an ultraviolet the structure of the product was 2-deoxy-1, 3, 4, 5-tetra-O-acetyl -L-sorbopyranos-2, 3-ene (II) or -1, 2-ene.…”
Section: ) Sorboses Part VIIImentioning
confidence: 99%